Cryptogenic ischemic stroke in cardiac transthyretin amyloidosis and sinus rhythm: a case report - Napolitano, Angela; Toffanin, Serena; Bulato, Cristiana; Campello, Elena; Simioni, Paolo; Spiezia, Luca (Frontiers in Cardiovascular Medicine, 2024)
Cardiac amyloidosis is a group of diseases characterized by the deposition of amyloid fibers in cardiac tissue. Two forms are mainly reported: light chain (AL) and transthyretin (ATTR) amyloidosis. Among the complications of transthyretin amyloidosis there are thrombotic events and, to a lesser extent, hemorrhagic events. The latter are likely caused by perivascular amyloid deposition resulting in capillary fragility, in addition to INR lability during anticoagulant therapy. The onset of thrombotic events may be caused by the high prevalence of atrial fibrillation (AF), mechanical cardiac dysfunction and atrial myopathy observed in patients with transthyretin amyloidosis. It remains unclear why thromboembolic events occur even in patients with sinus rhythm or adequate anticoagulation, though a hypercoagulable state or underlying inflammation may be involved. We report a case of cryptogenic ischemic stroke in an 86-year-old woman with transthyretin amyloidosis and sinus rhythm. Traditional coagulation tests, whole blood rotational thromboelastometry and impedance aggregometry did not show a hypercoagulable state. The thrombin generation assay did not reveal a prothrombotic state. However, the study of extracellular vesicles highlighted underlying immune-mediated endothelial damage likely responsible for the thrombotic diathesis. It could be hypothesized that inflammation plays a role in the hypercoagulability of patients with transthyretin amyloidosis. Larger prospective studies are needed to validate our hypothesis.